An Efficient OFDM-Based Monostatic Radar Design for Multitarget Detection - Delamou, Mamady; Noubir, Guevara; Dang, Shuping; Amhoud, El Mehdi (IEEE access, 2023)
In this paper, we propose a monostatic radar design for multitarget detection based on orthogonal-frequency division multiplexing (OFDM), where the monostatic radar is co-located with the transmit antenna. The monostatic antenna has the perfect knowledge of the transmitted signal and listens to echoes coming from the reflection of fixed or moving targets. We estimate the target parameters, i.e., range and velocity, using a two-dimensional (2D) periodogram. By this setup we improve the periodogram estimation performance under the condition of low signal-to-noise ratio (SNR) using Zadoff-Chu precoding (ZCP) and the discrete Fourier transform channel estimation (DFT-CE). Furthermore, since the dimensions of the data matrix can be much higher than the number of targets to be detected, we investigate the sparse Fourier transform-based Fourier projection-slice (FPS-SFT) algorithm and compare it to the 2D periodogram. An appropriate system parameterization in the industrial, scientific, and medical (ISM) band of 77 GHz, allows to achieve a range resolution of 30.52 cm and a velocity resolution of 66.79 cm/s.